ERK5 and its role in tumour development. (19th January 2012) - Lochhead, Pamela A.; Gilley, Rebecca; Cook, Simon J.
Abstract : The MEK5 [MAPK (mitogen-activated protein kinase)/ERK (extracellular-signal-regulated kinase) kinase 5]/ERK5 pathway is the least well studied MAPK signalling module. It has been proposed to play a role in the pathology of cancer. In the present paper, we review the role of the MEK5/ERK5 pathway using the 'hallmarks of cancer' as a framework and consider how this pathway is deregulated. As well as playing a key role in endothelial cell survival and tubular morphogenesis during tumour neovascularization, ERK5 is also emerging as a regulator of tumour cell invasion and migration. Several oncogenes can stimulate ERK5 activity, and protein levels are increased by a novel amplification at chromosome locus 17p11 and by down-regulation of the microRNAs miR-143 and miR-145 . Together, these finding underscore the case for further investigation into understanding the role of ERK5 in cancer.